Republic of Croatia : Staff Report for 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Until recently, Croatia's economic performance was the envy of many countries in transition: a successful stabilization effort in late 1993 was followed by virtual price stability and real GDP growth of 6 percent a year during 1994-97. Monetary tightening, the weak economy, and a drying-up of repatriated foreign savings exposed the underlying insolvency of a group of rapidly growing banks. Executive Directors emphasized that the task of restoring fiscal balance could not be accomplished without redressing the finances of the pension and health care systems.